MDR Escherichia coli carrying CTX-M-24 (IncF[F-:A1:B32]) and KPC-2 (IncX3/IncU) plasmids isolated from community-acquired urinary trainfection in Brazil - Juliana Buck Dias; João Gabriel Material Soncini; Louise Cerdeira; Nilton Lincopan; Eliana Carolina Vespero (Brazilian Journal of Infectious Diseases, 2022)
ABSTRACT: Acquired antibiotic resistance in bacteria has become an important worldwide challenge. Currently, several bacteria, including Escherichia coli, have multidrug resistance profiles. Genes such as bla CTX-M-24 and bla KPC-2 (carbapenemase) are widespread. This research letter reports about a genomic surveillance study where multidrug-resistant E. coli containing CTX-M-24(IncF [F-:A1:B32]) and KPC-2(IncX3/IncU) plasmids were obtained from community- acquired urinary tract infection in Brazil.